The relationship between the apnea-hypopnea index, oxygen desaturation index, average oxygen saturation, and body mass index in patients with obstructive sleep apnea - Novković, Dobrivoje; Popović, Nela; Novković, Nikola; Lukić, Jelena; Begović Kuprešanin, Vesna; Popević, Martin (Vojnosanitetski pregled, 2025)
Background/Aim. Obstructive sleep apnea (OSA) involves a range of conditions manifested as various forms of breathing disorders with intermittent complete breathing interruptions caused by obstruction in the upper airways. The disorder is more common in adult men, and obesity is a significant predisposing factor. The apnea-hypopnea index (AHI) is the main diagnostic criterion that reflects the frequency and duration of apneic phases. Besides the AHI, other parameters, such as the oxygen desaturation index (ODI), average oxygen saturation, and body mass index (BMI), may have diagnostic value. The aim of the study was to examine the correlation between AHI and ODI, AHI and average oxygen saturation, and AHI and BMI. Methods. A retrospective study included 200 patients, 166 men and 34 women, aged between 18 and 65, in whom OSA was proven by respiratory polygraphy. Depending on the AHI values, they were divided into three groups: Group I (AHI 5–15 events per hour), Group II (AHI 15–30 events per hour), and Group III (AHI > 30 events per hour). Results. There was a significant correlation between AHI and ODI in all groups, with the strongest correlation in Group III, where ODI also had predictive value for severe forms of apnea. Average oxygen saturation and BMI were significantly correlated with AHI only in Groups II and III. Conclusion. In addition to AHI, known as the main diagnostic parameter for OSA, ODI, average oxygen saturation, and BMI play a significant role in assessing apnea. With its strong correlation with AHI, as well as predictive value for more severe forms of apnea, ODI has the same importance as AHI in diagnosing and assessing the severity of this disorder.
Keywords: body mass index; oxygen saturation; prognosis; sleep apnea, obstructive